2001
DOI: 10.1523/jneurosci.21-19-07674.2001
|View full text |Cite
|
Sign up to set email alerts
|

Volume-Activated Chloride Currents Contribute to the Resting Conductance and Invasive Migration of Human Glioma Cells

Abstract: We used an in vitro model for glioma cell invasion (transwell migration assay) and patch-clamp techniques to investigate the role of volume-activated Cl(-) currents (I(Cl,Vol)) in glioma cell invasion. Hypotonic solutions ( approximately 230 mOsm) activated outwardly rectifying currents that reversed near the equilibrium potential for Cl(-) ions (E(Cl)). These currents (I(Cl,Vol)) were sensitive to several known Cl(-) channel inhibitors, including DIDS, tamoxifen, and 5-nitro-2-(3-phenylpropylamino)-benzoate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
170
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(181 citation statements)
references
References 65 publications
(115 reference statements)
9
170
0
1
Order By: Relevance
“…Previous studies revealed that ion channels and transporters are essential for cell volume regulation and invasive migration of some human tumors (19,20). We proposed that transmembrane water efflux through aquaporin water channels facilitates cell volume change mediated by net salt efflux through ion channels and transporters in the migrating colon cancer cells, leading to enhanced motility and invasion.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies revealed that ion channels and transporters are essential for cell volume regulation and invasive migration of some human tumors (19,20). We proposed that transmembrane water efflux through aquaporin water channels facilitates cell volume change mediated by net salt efflux through ion channels and transporters in the migrating colon cancer cells, leading to enhanced motility and invasion.…”
Section: Discussionmentioning
confidence: 95%
“…Ransom et al (2001) found that in glioma cells that change shape or that migrate, the I Cl,Vol currents are activated. If these currents are blocked by NPPB or tamoxifen, glioma cell migration is inhibited without affecting survival rate of these cells.…”
Section: Shape Changesmentioning
confidence: 99%
“…First described by , a chloride conductance exists in glia-derived tumor cells from humans and animals Ransom et al, 2001). It is not found in normal cells, and the current displayed slight outward rectification, time-and voltage-dependent inactivation, as well as block by tamoxifen.…”
Section: Voltage-gated Chloride Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting other ion channels, besides gBK channels, could include chloride channel-1 (CLIC1 or its other alias, CLCA1) or aquaporins. Both chloride channel-1 and aquaporins are also overexpressed in glioma (41)(42)(43). BK channel activation leads to cell swelling, whereas CLIC1 activation leads to cell shrinkage (7,8,44).…”
Section: Discussionmentioning
confidence: 99%